Identification of Vaname Shrimp Marketing Strategies for Pond Farmers in Napalakura Village, Napabalano District, Muna Regency - Sufiana Sufiana; La Karimuna; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
The objectives of this study were (1) to determine the income of Vaname shrimp farmers; and (2) knowing the marketing strategy of Vaname shrimp in Napalakura Village, Napabalano District, Muna Regency. This research was conducted in July 2019 in Napalakura Village, Napabalano District, Muna Regency. The population in this study were all pond farmers in Napalakura Village, Napabalano District, Muna Regency, totaling 15 pond farmers. The sample for internal factors consisted of 15 pond farmers, the sample for external factors consisted of 3 consumers. SWOT analysis is used to determine the strategy. The results showed that vaname shrimp farmers had an average production of 1,100 kg/2 ha with a selling price of Rp 38,000 / kg. Farmers' income is IDR 41,800,000 / 2 Ha. Total fixed costs are IDR 100,000 / 2 and variable costs IDR 12,600,000 / 2 Ha, and expenses of IDR 13,020,000 / 2 Ha. The total income earned by vaname shrimp farmers is IDR 27,780,000 / 2 Ha. The analysis of internal factors resulted in an IFAS of 3.15. Vaname shrimp farmers in Napalakura Village, have very good strength in their operations. External analysis factor of 3.65 for the EFAS matrix. This indicates that the van name shrimp farmers in Napalakura Village are in a very good position to further develop the cultivation, but it does not rule out the possibility of being alert to the existing threats.